Being and Becoming a Monk on Mount Athos: An Ontological Approach to Relational Monastic Personhood in the "Garden of the Virgin Mary" as a Rite of Passage - Paganopoulos, Michelangelo (Open theology, 2020)
This paper brings together ethnography as practice research, and theology as experiential theory, towards an ontological interdisciplinary understanding of relational personhood on Mount Athos. The first part of the paper consists of ethnographic data gathered from the field, approaching monastic life as a rite of passage to heaven, and using the anthropological discourse of the "sacred" to represent and interpret this passage in sociological and moral terms. The second part of the essay expands on this empirical material by following the two "fundamental" elements of personhood, Freedom and Otherness, in the respective Christological discourses of Zizioulas and Yannaras. The aim of the second part is to ontologically expand on the experience of relational personhood by approaching theology as a kind of practice ["theoro" as "I-see-God" via practices of faith] that takes us to deeper levels of understanding of being and becoming, in relation both to the invisible God and the visible, material World. In this context, the focus of the paper gradually moves from the Athonian landscape. informed by the energies of God that run through it, to Athonian personhood as defined by the personal and ontological relation of each monk to the landscape, which includes themselves, in an ontologically relational manner. As I argue, this relational ontology extends from the grace received in everyday practices by all the monks to the charismatic personalities, whose individual agency and freedom from nature enabled them to change Athonian history and become emblems of the contemporary ideals of monastic life as a dialectical symbiosis within God and nature.